Zuogui Wan alleviates ovariectomy-induced osteoporosis by maintaining FoxO3 and increasing NK1R: Zuogui Wan alleviates ovariectomy-induced osteoporosis - Li, Xing; Tan, Feng; Wu, Dan; Mai, Congying; Guan, Huaquan; Fan, Qiaoling (Cellular and Molecular Biology, 2023)
Sixty Sprague-Dawley female rats were randomly divided into sham-operated groups and five ovariectomy (OVX) subgroups. Rats subjected to sham and OVX were treated with the vehicle, alendronate, and Zuogui Wan (ZGW) at the doses of low, medium and high lyophilized powder daily for 3 months, respectively. The gene or protein expression of NK1R, PPAR γ, and OSX were assayed by either quantitative polymerase chain reaction or Western blot analysis. The results showed that compared with the OVX group, ZGW could reduce the level of PPARγ and increase the levels of OSX and. Meanwhile, ZGW could prevent bone loss. In addition, we found ZGW upregulated for the NK1R mRNA or protein expression by promoting the expression level of transcription factor FoxO3 and increasing its binding to the NK1R promoter region -700/-200 sequence. These results suggest that the regulation of FoxO3 and NK1R played a role and contributed to the mechanism of ZGW underlying the increase in bone mass in the OVX rat model.